1998
DOI: 10.1159/000009999
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Assay of Iron in Ovarian Cysts: A New Diagnostic Method to Evaluate Endometriotic Cysts

Abstract: CA-125 is abundantly secreted from ovarian endometriotic cysts, but is not specific to endometriosis. In order to develop a new, more specific diagnostic marker for endometriosis, the iron concentrations in various ovarian cysts were assayed. The ovarian cysts were punctured and the contents aspirated laparoscopically, laparotomically, or transvaginally. The iron concentration in the ovarian cystic fluid was assayed using a spectrophotometer after protein precipitations and chromogen treatment. The iron concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…al. [40] have reported that endometriotic cyst iron content ranges from 100–1.7 mM. Patients with endometriosis who develop endometriomas may have heavy or prolonged bleeding into these cysts and peritoneal implants thus exposing more heme proteins to HOCl generated locally by MPO leading to the generation of free iron mediated by HOCl-hemeprotein heme destruction [8, 31, 33, 41].…”
Section: Discussionmentioning
confidence: 99%
“…al. [40] have reported that endometriotic cyst iron content ranges from 100–1.7 mM. Patients with endometriosis who develop endometriomas may have heavy or prolonged bleeding into these cysts and peritoneal implants thus exposing more heme proteins to HOCl generated locally by MPO leading to the generation of free iron mediated by HOCl-hemeprotein heme destruction [8, 31, 33, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Other tumor markers, metabolites, or hormones such as CEA, Ca 125, Ca 19.9, alphafetoprotein, progesterone, or iron can also be assayed, 18,19 but they lack sensitivity and specificity. In our series, 81.2% of follicular cysts had an E2 content Ͼ4,000 pg/ml (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Endometriotic cysts contain a huge amount of free iron. The concentration exceeds 100 nmol/L, which is up to 10 000‐fold higher than the concentration normally present in serum (0.013–0.027 mmol/L) . Accordingly, massive iron staining has also been observed in the stroma of the cyst, mostly located in macrophages .…”
Section: Introductionmentioning
confidence: 93%